Effects of iron supplementation starting from early gestation in non-anemic pregnancy and neonatal birth outcomes - Preeyaporn Jirakittidul (2018)
© 2006 Institute of Research and Development, Suranaree University of Technology. Iron supplementation, as early as possible, is commonly recommended for all pregnant women in developing countries to reduce maternal anemia. However, this excessive iron can induce a high hemoglobin level and negatively influence neonatal outcomes. The objective of the present study is to assess the impact of iron supplementation starting from early pregnancy and neonatal birth outcomes. All data in the present retrospective cohort study were obtained from the antenatal records and labor registry of non-anemic pregnant Thai women who attended their first antenatal care and delivery at Vajira Hospital, Bangkok, Thailand between June 2006 and December 2007. The proportions of low birthweight (LBW), small for gestational age (SGA), and preterm delivery were compared between the early supplement group which started oral iron before 16 weeks of gestation and the control group which started later. Among 880 non-anemic pregnancies, there were 477 women in the early supplement group and 403 women in the control group. The incidence of LBW in the early supplement group was significantly lower than in the control group (5.5% vs. 9.4%, risk ratio: 0.58; 95%confidence interval: 0.37-0.94). There were no significant differences in the occurrence of SGA and preterm delivery between groups. Iron supplementation starting from early gestation in non-anemic pregnancy has a significant benefit in reducing the incidence of LBW.